Citizenship at the Margins: Exploring Participation as 'Right to the City' in Vizhinjam, Kerala. (November 2019) - Ganga, Aarathi
This article explores the nature of urban citizenship among fishers in Kerala, one of the state's most marginalised communities, by analysing their participation in a centrally sponsored slum rehabilitation programme—Rajiv Awas Yojana (RAY)—in Vizhinjam, Thiruvananthapuram. The 'right to participate' is considered an integral part of the 'right to the city', and the inability of the fishing community to participate in the decision-making processes of urban development programmes that directly affect their lives reveals the exclusionary nature of their citizenship. In a state that is renowned for its achievements in human development and governance, the fishing community continues to be marginalised and lack collective power to influence policies. Participatory meetings in such contexts become tokenistic, and their transformative capacity is undermined. The inefficiency of participatory meetings organised under RAY also stems from the powerlessness of local governments to alter urban programmes designed by national governments.